Adaptive value and competitive ability of ryegrass resistant and susceptible to iodosulfuron in competition with wheat - Mariani, Franciele; Vargas, Leandro; Agostinetto, Dirceu; Nohatto, Marcos André; Langaro, Ana Claudia; Duarte, Thiago Vieira (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to identify and compare adaptive values of ryegrass (Lolium multiflorum) biotypes resistant and susceptible to the herbicide iodosulfuron and to evaluate their competitive ability with wheat (Triticum aestivum). To evaluate the adaptive value, the biotypes were sown in pots and collected every 10 days after emergence, up to 80 days. At each collection, height, leaf area, and dry matter of shoots were assessed, and, from these evaluations, indirect variables were calculated to compare the growth between the biotypes. The competitive ability was determined in a replacement series experiment, varying the proportion of the culture and of the competitor. The proportions tested were: 100:0 (wheat in pure stand), 75:25, 50:50, 25:75, and 0:100% (resistant or susceptible ryegrass biotype under pure stand); the evaluated variables were leaf area and dry matter. The results of the comparative studies of growth showed similarity between ryegrass biotypes resistant and susceptible to iodosulfuron, which does not characterize pleitropic effect due to resistance. Regarding competitive ability, interspecific competition is harmful to the resistant biotype, whereas, for the susceptible biotype, there is no effect of the competitor. The wheat crop shows greater competitive ability than resistant and susceptible ryegrass biotypes.
Keywords: Lolium multiflorum; Triticum aestivum; interspecific weed competition; herbicide; weed